Citizens' Opinions of and Experiences with Government Responses to COVID-19 Pandemic in Viet Nam - Huyen Thanh Do; Cuong Viet Nguyen; Long Thanh Nguyen; Phuong Minh Nguyen; Quyen Ha Ngo; Tung Duc Phung (Global Labor Organization (GLO), 2022)
This study explores the impact of COVID-19 and how Vietnamese citizens perceived and experienced measures adopted by central and local governments to contain the CVODI-19 pandemic in 2021. In general, the COVID-19 pandemic had a more severe impact in 2021 than in 2020. Citizens showed great concern about their children's education (76 percent) and their personal health (68 percent). COVID-19 negatively impacted employment and income, with 77 percent of the respondents reporting income reduction due to the pandemic. The poor, ethnic minorities, unskilled, non-farm workers, and those working in the service sector or living in provinces with longer lockdowns were the most likely to suffer. Compared with 2020, in 2021, respondents showed a high but declining positive assessment of government performance in dealing with the pandemic, with 84 percent of the respondents rating the responses from the Central Government as good or very good (97 percent in 2020), 89 percent rating the response from their provincial governments' responses as good or very good (94 percent in 2020). Only 13 percent of the respondents received support from the Government's package. However, ethnic minorities, female, poorer and rural respondents were less likely to receive the support. For the support recipients, delivery was regarded as timely and transparent, but administrative procedures to get access to the package were not simple. Meanwhile, support from non-governmental organizations (NGOs), social organizations, charity foundations, and individuals was distributed more efficiently, with 25 percent of the respondents receiving support from these sources.
Keywords: 330; COVID-19; government policy; citizens' opinions; aid package; Vietnam